Implementation of land title registration system in Malaysia: lessons for Hong Kong - Wu, Richard; Zul Kepli, Mohd Yazid (Malayan Law Journal Sdn Bhd, 2011)
Hong Kong is one of few common law jurisdictions that still adopt deeds registration system, rather than the system of registration of title. The (Cap 128) was enacted in 1844 and is the oldest piece of legislation still in use in Hong Kong. The system is costly and time consuming as lawyers have to review title deeds for every property transaction to verify that the title is good. In contrast, the system of registration of title, like the Torrens system adopted in Australia, will enable lawyers to establish conclusive evidence of ownership and interests in the property by conducting a search at the land title register. In fact, Malaysia has implemented such a system back in the 19th century and the current registration of title legislation, the , was adopted as early as in 1965. In the past few decades, the registration of title system has become an international trend in land administration. Both United Nations and the World Bank recommended the adoption of such system. Hong Kong is desirous of following such international trend and in 2004, its government adopted the (LTO), paving the way for the transition of a deed registration system to a registration of title system in the near future. While Malaysia and Hong Kong have their own distinctive political, economic and social characteristics, there are common legacies shared by both jurisdictions. For example, both places were former British colonies, with Malaysia becoming independent in 1957 and Hong Kong reuniting with China in 1997. They both use common law inherited from Britain. The two governments also look to each other for inspiration in other reform initiatives like anti-corruption and financial development. In this article, the authors first presented an overview of the registration of title system under the Malaysian land law. They then examined the implementation experience of registration of title system in Malaysia and evaluated the lessons Hong Kong could learn in its future implementation of the registration of title system.